Recording of Students' Health Identification and Personal Health Record - Pradea Wulandari; Riski Aryanti (Indonesian Journal of Global Health Research, 2025)
Children's health at school is a crucial aspect in supporting the learning process and student development. At SDN 002 Penajam, attention to students' health is a top priority in creating a healthy and productive learning environment. However, managing students' health often faces challenges, such as the lack of a structured and consistent record-keeping system. Objective: The study aimed to determine how the personal medical record keeping of students is conducted at SDN 002 Penajam.Method: Data collection in this study is conducted using documentation methods, followed by data processing and analysis.Results: From the results of the interviews, it was found that SDN 002 Penajam has a student checkbook that records students' height and weight measurements during school health checks, but does not have a record book for students' medical history.Conclusions: The study on personal medical recordkeeping of students at SDN 002 Penajam reveals that the systematization of student health data is crucial in supporting administrative and documentation aspects in schools. Organized medical records enable teachers and school health unit (SHU) managers to easily store and access students' health information.